Compliance of Nurses Working in Emergency Services and Intensive Care Units to Isolation Precautıons in Covid-19 Pandemic and Health Anxiety Levels - Ela Yılmaz Coşkun; Nilüfer Berberkayar (Hemşirelikte Araştırma Geliştirme Derneği, 2023)
Aim: Nurses faced with some physical and mental problems fighting on the front line in the Covid-19 pandemic. In this difficult fighting, it is important to compliance of nurses with the isolation precautions both in terms of their health and the speed of contagion. It was aimed to examine the nurses' compliance with the isolation precautions the pandemic and the level of health anxiety.Methods: It is descriptive and relationship type. It was carried out with nurses working in emergency service and intensive care units in a state university training and research hospital in Turkey between November-December 2020 (N = 116). The rate of participation of nurses in the study is 88.8% (n = 103) regardless of choosing a sample. The data obtained with the questionnaire form, "Compliance Scale to Isolation Precautions" and "Health Anxiety Scale". The data obtained were analyzed using descriptive, parametric, and nonparametric statistical methods in SPSS 23.0 package data program. Results: In the study; the compliance of nurses with isolation precautions was found to be higher than in the literature. It was found that the health anxiety levels of the nurses were low. In addition, no significant relationship was found between the two scales. Conclusions: It is recommended regularly to plan training programs that will increase nurses' compliance with isolation precautions and reduce anxiety and to conduct the study based on observation in a larger sample group.